2010
DOI: 10.1128/ec.00373-09
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Developmental Effects Resulting from Deletion of thecitAGene Encoding Citrate Synthase in Aspergillus nidulans

Abstract: Citrate synthase is a central activity in carbon metabolism. It is required for the tricarboxylic acid (TCA) cycle, respiration, and the glyoxylate cycle. In Saccharomyces cerevisiae and Arabidopsis thaliana, there are mitochondrial and peroxisomal isoforms encoded by separate genes, while in Aspergillus nidulans, a single gene, citA, encodes a protein with predicted mitochondrial and peroxisomal targeting sequences (PTS). Deletion of citA results in poor growth on glucose but not on derepressing carbon source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
0
14
0
3
Order By: Relevance
“…AcuJ-GFP was detected using mouse anti-GFP (at 1/4,000) and anti-mouse IgG-horseradish peroxidase ([HRP] at 1/4,000) antibodies (Promega Corp.) as primary and secondary antibodies, respectively. Anti-␣-tubulin was used to detect ␣-tubulin as a loading control as previously described (39). Signals were detected using Fujifilm image reader LAS-3000 (Berthold Australia Pty Ltd).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…AcuJ-GFP was detected using mouse anti-GFP (at 1/4,000) and anti-mouse IgG-horseradish peroxidase ([HRP] at 1/4,000) antibodies (Promega Corp.) as primary and secondary antibodies, respectively. Anti-␣-tubulin was used to detect ␣-tubulin as a loading control as previously described (39). Signals were detected using Fujifilm image reader LAS-3000 (Berthold Australia Pty Ltd).…”
Section: Methodsmentioning
confidence: 99%
“…Strains were incubated for 45 min to 1 h with 25 to 50 nM MitoTracker Red CMXRos (Invitrogen) before being fixed as previously described (61). Confocal microscopy was performed as described previously (39).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported the purification and characterization of the citrate synthase from A. nidulans (Maeng et al, 1993), and also have analyzed the nucleotide sequence of the citrate synthase gene, named citA, cloned from the chromosomespecific genomic library of this fungus (Park et al, 1997). It has also been reported that deletion of citA results in poor growth on glucose but not on derepressing carbon sources, and that methyl citrate synthase (McsA) can substitute for the loss of CitA activity (Murray and Hynes, 2010). In the present study, we isolated the cDNA of citA and analyzed its nucleotide sequence to confirm the primary structure of the citrate synthase.…”
mentioning
confidence: 70%